Characterization of NiO films deposited by homemade spin coater. (4th May 2016) - Taşköprü, T.; Turan, E.; Zor, M.
Abstract: NiO films were fabricated by sol–gel spin coating technique. The deposited films annealed in air, oxygen, nitrogen and argon atmospheres. The influence of the annealing atmospheres on the structural, morphological, optical and electrochemical features of the NiO films was investigated. The XRD studies revealed that the samples had nickel oxide cubic structure. The annealing of the samples in inert atmospheres leads to Ni phase formation in the structure. FESEM images showed that the heat treatments in inert atmosphere boost the larger clusters and crystallite size varying in the range 21–39 nm. Transmission of the films decreased from 85 to 20% as a function of annealing atmospheres. The electrochemical behavior of the films was studied by means of cyclic voltammetry in 0.3 M KOH solution. Cyclic voltammograms showed that anodic peak shift takes place for the films annealed in nitrogen and argon atmospheres. The findings in our study suggest that the physical properties of the NiO films strongly depend on the post annealing atmospheres. Graphical abstract: Highlights: The deposition of cubic NiO films was confirmed with XRD and FT–IR studies. Annealing in inert medium leads to change the crystal structure and morphology of NiO films. Transmissions of the films decreased from 85 to 20% as a function of annealing medium. Cyclic voltammetry showed that anodic peak shift takes place for the film annealed in inert atmospheres.